Biodegradation, decolourisation and detoxification of textile wastewater enhanced by advanced oxidation processes - Ledakowicz, Stanislaw; Solecka, Monika; Zylla, Renata (Journal of biotechnology, 2001)
Recently, an increasing application of so called advanced oxidation processes (AOPs) to industrial wastewater has been observed. In particular, an integrated approach of biological and chemical treatment of wastewater is advantageous conceptually. The subject of our study was synthetic wastewater, simulating effluents from knitting industry. The wastewater contained components that are very often used in Polish textile industry: an anionic detergent Awiważ KG conc., a softening agent Tetrapol CLB and an anthraquinone dyestuff—Acid Blue 40, CI 2125. The toxicity of the detergents and the dye was determined in terms of effective concentration EC 50 using mixed cultures of activated sludge as well as pure culture of luminescent bacteria Vibrio fischerii NRRLB-11177. The dye did not undergo biodegradation without AOPs pretreatment, therefore a degree of its removal (decolourisation) by the AOPs has been determined and its bio-sorption properties on the flocks of activated sludge have been studied. The dye adsorption onto flocks of activated sludge was described by Henry's isotherm. Our investigations focussed on the influence of various oxidants like O 3, H 2O 2 and UV light on biodegradation of single components aqueous solution as well as of the whole textile wastewater. The results of kinetic measurements of the biodegradation (by means of acclimated activated sludge) was described by Monod type of kinetic equation. The experimental evidence of the positive effect of chemical oxidation pretreatment on the biodegradation of recalcitrant compounds was quantified by estimation of the kinetic parameters of the Monod equation. Due to the AOPs pretreatment a decrease of the Monod constant and an increase of maximal specific growth rate was observed. The activity of degradative enzymes of activated sludge was assayed by the methods of 2-[4-iodophenyl]-3-[4-nitrophenyl]-5-phenyltetrazolium chloride test.